In a Competitive Market, Improving HRM to Assess Cooperative Opportunities and Challenges Indonesia's 2045 Economic Battle - Abdul Wahab Samad; Afiat, Dominica Dini; Ishaq, Muhammad; Hasibuan, Ahmad Nurdin (Jurnal Multidisiplin Madani, 2023)
This study examines cooperatives' opportunities and challenges in the industrial era 4.0 by strengthening human resource management to manage market changes caused by the 4.0 competition war in the Indonesian economy in 2045, which affects all aspects of digitalization in cooperative organizations. Business intelligence is also needed to evaluate high-tech breakthroughs in the exchange of design and innovation knowledge and supplier and customer behavior data, which will be conveyed in Industry 4.0. The troubling method approach was used for this study to examine causal relationships, listen to information from multiple parties, and find appropriate solution ideas through a qualitative narrative study. The study found that Indonesian cooperatives require more planning and finance to realize their full potential. The Indonesian economy will be built on this innovation in 2045 to achieve cooperative economic goals. Cooperatives need confidence in their role in the digital platform transformation ecosystem, which requires close collaboration that benefits suppliers and customers